1981
DOI: 10.1002/1097-0142(19810401)47:7<1863::aid-cncr2820470724>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Small-cell carcinoma of the lung—survival according to histologic subtype: A veterans administration lung group study

Abstract: Six-hundred-twenty cases of small-cell carcinoma of the lung entered into the Veterans Administration Lung Group protocols 9-15 were retrospectively subdivided into histologic subtype, as proposed by the WHO (1977). Medium survival was greater for subtype No. 21 (lymphocyte-like) than for subtype No. 22 (intermediate) (17.2 vs. 12.6 weeks; P = .005). Patients with extensive disease survived longer with subtype No. 21 than subtype No. 22 (14.5 vs. 10.9 weeks; P = .026). However, no median survival difference wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The numbering of these criteria is used in the same way throughout this paper. The criteria are grouped together because of assumed associations with particular tumour types: criteria 1-4 with squamous carcinoma, [5][6][7][8][9][10][11][12][13] with small cell carcinoma, and 14-18 with adenocarcinoma. Definitions of the diagnostic criteria and diagnostic categories are listed in appendix 4. Eighty biopsy specimens of lung cancer were retrieved from the departmental files of the participating pathologists; contemporaneous cytological specimens and resection specimens were also available.…”
Section: Methodsmentioning
confidence: 99%
“…The numbering of these criteria is used in the same way throughout this paper. The criteria are grouped together because of assumed associations with particular tumour types: criteria 1-4 with squamous carcinoma, [5][6][7][8][9][10][11][12][13] with small cell carcinoma, and 14-18 with adenocarcinoma. Definitions of the diagnostic criteria and diagnostic categories are listed in appendix 4. Eighty biopsy specimens of lung cancer were retrieved from the departmental files of the participating pathologists; contemporaneous cytological specimens and resection specimens were also available.…”
Section: Methodsmentioning
confidence: 99%
“…Using the presence of significant host response and/or the presence of large cell carcinoma as a criterion for the diagnosis of the intermediate subtype of SCCL, a longer survival for patients with oat-cell carcinoma was reported in a large study of 620 patients with SCCL treated with chemotherapy in the study by VALG. 6 It is concluded from the current study that a high degree of unanimity among different panelists is possible in the diagnosis of SCCL. Almost 10% of small cell tumors provoke significant problems in the light microscopic interpretation, particularly tumors demonstrating transition to large cell carcinoma, and those with squamous cell differentiation and/or glandular components.…”
Section: Cancer October 1 1982mentioning
confidence: 67%
“…*-lo Neither was any difference in survival between the morphologic subtypes reported from studies performed at the National Cancer Institute, USA, where a modified W H O classification was Members of the Veterans Administration Lung Group Study (VALG) have reported that patients with the "oat-cell" subtype had a longer survival after chemotherapy than patients with the "intermediate" cell type. 6 After 14 years' experience with the first classification, a revised WHO classification of lung tumors was recommended in 198 1 . *' SCCL was divided into three subtypes: "oat-cell,'' "intermediate," and "combined SCCL."…”
mentioning
confidence: 99%
“…Currently, lung cancer can be divided into two types according to the degree of differentiation and morphological characteristics: small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC). NSCLC includes three subtypes: squamous cell carcinoma, adenocarcinoma and large cell carcinoma [9]- [13]. Timely diagnosis of lung cancer type is of great clinical significance to help doctors develop effective treatment programs and improve patients' survival time and quality of life.…”
Section: Introductionmentioning
confidence: 99%